Geographic variation in population structure and grazing features of Calanus glacialis/marshallae in the Pacific Arctic Ocean - Ishihara, Minami; Matsuno, Kohei; Tokuhiro, Koki; Ando, Yasuhiro; Sato, Kazutoshi; Yamaguchi, Atsushi (Frontiers in Marine Science, 2023)
Calanus glacialis/marshallae, is a dominant zooplankton species in the Pacific Arctic Ocean, that is widely distributed in shelf areas, and it plays a vital role in connecting primary production withto higher trophic levels. TheirIts phenology is well adapted to hydrography, but there is little available information is available onabout regional and diel changes in the population structure and grazing features. In this study, we investigated C. glacialis/marshallae during autumn 2019 in the Eastern and North-EasternNortheastern Chukchi, and Canada BasinCanadian basins to reveal geographic and diel variations in population structure, body size, grazing activity, and fatty acid composition. The abundance of C. glacialis/marshallae was found to be high on the slopes and low on the shelves. Since bodyBody size (prosome length) was well described by the Bĕlehrádek equation combined with in-situ temperature throughout the sampling region. Cluster analysisanalyses based on hydrographic parameters waswere divided into four regions: the southern shelf, northern shelf, slope, and basin. The southern shelf was dominated by copepodite stage five (C5), which was) transported from the Bering Sea by Pacific waters. On the northern shelf, C4 and C5 were dominant, on the northern shelf, suggesting that they grew more slowlyslower than the populationthose on the southern shelf. Additionally,, and the populationpopulations also exhibited a higher concentrationconcentrations of fatty acids originating from dinoflagellates than those inoriginating from the pan-Arctic Ocean, indicating low productivity in the region. The population on the slope population showedhad the highest abundance, C4 dominancewas dominant, and large amounts of diatom-derived eicosapentaenoic acid (EPA). These features wereare attributed to the upwelling of populations and nutrients that supportedsupport diatom growth. In the basin, the early copepodite stages of composition were distinctly higher than those recorded in previous studies, because larger amounts of organisms inflowedflow into the region, resulting in more extended reproduction periods. In the basin, small and large forms inof C5 were found simultaneously found, and the small form exhibited a diel pattern in grazing activity pattern, but the large forms did not. These findings suggest their well adaptation in changing of the Pacific Arctic Ocean.